2019
DOI: 10.5455/msm.2019.31.277-281
|View full text |Cite
|
Sign up to set email alerts
|

Development of Mother's Postnatal Sense of Security

Abstract: Introduction: Although sense of security in mothers is not clearly specified in literature, most important factors that make it up in women that do not have issues in pregnancy are social support, prenatal health care and partner's support. Psychological factors play a key role in recognizing fear of childbirth, distinguishing anxiety from clinical depression. Recognizing risk factors and adequate intervention support would significantly reduce fear. Aim: to analyze development of mother's sense of security du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
2
4
0
2
Order By: Relevance
“…A atitude e participação do companheiro ao longo da gravidez, incluindo as aulas pré-natais, poderá contribuir para uma melhor gestão da dor de trabalho de parto e para tornar esta experiência num evento de vida positivo, com repercussões na percepção de segurança no pós-parto. 1,2,14 Aliado a isto, a partilha de responsabilidades, sobretudo no pósparto e direcionada aos cuidados à criança, apoiando a aquisição de competências relaciona-se com a promoção da segurança materna. 17 Remetendo os dados para as variáveis obstétricas, as grandes constatações são relativas à paridade, com as mulheres multíparas a apresentarem maior percepção de segurança no pós-parto.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…A atitude e participação do companheiro ao longo da gravidez, incluindo as aulas pré-natais, poderá contribuir para uma melhor gestão da dor de trabalho de parto e para tornar esta experiência num evento de vida positivo, com repercussões na percepção de segurança no pós-parto. 1,2,14 Aliado a isto, a partilha de responsabilidades, sobretudo no pósparto e direcionada aos cuidados à criança, apoiando a aquisição de competências relaciona-se com a promoção da segurança materna. 17 Remetendo os dados para as variáveis obstétricas, as grandes constatações são relativas à paridade, com as mulheres multíparas a apresentarem maior percepção de segurança no pós-parto.…”
Section: Discussionunclassified
“…7 Os profissionais de saúde, especialmente os enfermeiros obstétricos, precisam compreender os fatores que condicionam a percepção de segurança materna neste período com o propósito de promover uma transição para a parentalidade positiva. 14 Assim, o objetivo deste estudo foi identificar os fatores que interferem com a percepção de segurança materna no pós-parto.…”
Section: Introductionunclassified
“…Specifically, the support provided multiple opportunities for dialog with childcare support advisers and public health nurses, and the “property” of proactive involvement in pregnancy, childbirth, and child-rearing was strengthened by the provision of informative health counseling and the encouragement of self-reflection. Previous studies have revealed that the sense of security during the first week after birth is statistically significantly greater in mothers whose husbands actively participated in psychophysical preparation for childbirth together with them [ 22 ]. In addition to family participation in child-rearing, having someone other than family members to consult with about child-rearing and to turn to in times of need can lead to a sense of security, and may promote proactive involvement in child-rearing.…”
Section: Discussionmentioning
confidence: 99%
“…Parents' postnatal sense of security is closely related to the situation of pregnancy and childbirth and is described as a part of the overall experience of childbirth [7,8]. Recently, a number of studies on parents' postnatal sense of security have been carried out around the world, and researchers have found that certain intervention measures could improve the level of parents' postnatal sense of security, for example, participating in pre-delivery physical and mental education can improve parents' postpartum sense of security [9]. In fact, there are many factors that affect the parents' postnatal sense of security.…”
Section: Discussionmentioning
confidence: 99%